1981
DOI: 10.1103/physrevb.23.37
|View full text |Cite
|
Sign up to set email alerts
|

Photochromism of three photosensitive Fe centers in SrTiO3

Abstract: Three paramagnetic Fe defect complexes have been observed by electron-spin resonance in chemically reduced crystals of SrTi03. These are identified as (1) in Fe + ion substituted on a Ti site with a nearby charge-compensating interstitial impurity, and (2) and (3) two charge states of substitutional Fe with a near-neighbor oxygen v icancy, Fe +-Vp and Fe'+-&p. These three defects are related in the sense that photoexcitation can reversibly switch electrons between the vacancy-associated and interstitial-associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
1

Year Published

1986
1986
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(16 citation statements)
references
References 22 publications
2
13
1
Order By: Relevance
“…The electronic configurations of acceptor-doped (particularly in Fe 3+ -doped or Cr 3+ -doped) SrTiO 3 are shown in Refs. [7][8][9][10][11][12][13]. Donor (Nb 5+ ) doping could lower the resistance; however, the sensitivity could decrease, as shown in Fig.…”
Section: Resultsmentioning
confidence: 94%
“…The electronic configurations of acceptor-doped (particularly in Fe 3+ -doped or Cr 3+ -doped) SrTiO 3 are shown in Refs. [7][8][9][10][11][12][13]. Donor (Nb 5+ ) doping could lower the resistance; however, the sensitivity could decrease, as shown in Fig.…”
Section: Resultsmentioning
confidence: 94%
“…The other centre at 1846 G (g ∼ 3.82) is also characteristic of a defect that is in an octahedral field with a very strong tetragonal distortion, except that S = 3/2 [33][34][35]. Following our earlier arguments, the fact that g ⊥ ∼ 3.82 strongly suggests that D h .…”
Section: Epr Spectroscopymentioning
confidence: 73%
“…1͑c͒ and 2͑c͒. 20,24,30,31 Measurements made over a wide magnetic field range showed no evidence of Fe 2+ V O in either annealed or unannealed samples, however, low temperature studies without illumination revealed the presence of Fe 4+ V O . However, the Fe 5+ spectrum increases in intensity by 1.5 compared with that observed in the dark.…”
Section: Resultsmentioning
confidence: 96%